Quantifying timeframes for transitioning the management of a fresh release of LNAPL petroleum from active recovery to natural source zone depletion: Evidence from intensive field investigation of a new diesel release - John L. Rayner; Mike J. Donn; Andrew King; Kaveh Sookhak Lari; Greg B. Davis (Water Research, 2026)

Quantifying timeframes for transitioning the management of a fresh release of LNAPL petroleum from active recovery to natural source zone depletion: Simulation of a new diesel release - Kaveh Sookhak Lari; Greg B. Davis; John L. Rayner; Mike J. Donn (Journal of Environmental Management, 2026)

State of the UK Climate in 2025 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Nick Rayner; Ségolène Berthou; Lucy Barker; Steve Turner; Jamie Hannaford; Svetlana Jevrejeva; Andrew Matthews; et al. (International Journal of Climatology, 2026)

In situ XANES study of PFAS impacted soils filled with aqueous and non-aqueous phases - Anand Kumar; Md Khairul Alam; Bin Qian; Mike J. Donn; Divina A. Navarro; John L. Rayner; Greg B. Davis; Bruce Cowie; Bobby Pejcic; Steve Fisher (Journal of Contaminant Hydrology, 2026)

Public support for food subsidy and tax scenarios to promote healthy and sustainable diets: Evidence from deliberative forums in two UK locations - Hannah Forde; Peter Scarborough; Lucy Yates; Jessica Renzella; Mark Sheehan; John Buckell; Alice O’Hagan; Sian Taylor; Jane Ward; Annie Connolly; Mike Rayner; Richard Smith; et al. (Food Policy, 2025)

Assessment of sealants for the mitigation of PFAS leaching from contaminated concrete - Grant B. Douglas; Prashant Srivastava; Rai Kookana; Mike Williams; Greg B. Davis; John Rayner; Canh Tien Trinh Nguyen; Sonia Mayakaduwage; Jason K. Kirby (Journal of Hazardous Materials, 2025)

Intercomparison of in-well, depth profile and online soil gas measurements for estimating petroleum natural source zone depletion rates: Will in-well gas samples suffice? - Greg B. Davis; John L. Rayner; Mike J. Donn; Trevor P. Bastow; Andrew Furness; Yasuko Geste; Andrew King (Journal of Hazardous Materials, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Retraction notice to “Effects of environmental impact and nutrition labelling on food purchasing: An experimental online supermarket study” [Appetite 180 (2023) 106312] - Christina Potter; Rachel Pechey; Brian Cook; Paul Bateman; Cristina Stewart; Kerstin Frie; Michael Clark; Carmen Piernas; Mike Rayner; Susan A. Jebb (Appetite, 2025)

Natural Source Zone Depletion of crude oil, gasoline, diesel and aviation gasoline petroleum in the same soil/aquifer system – An intensive intercomparison field study and simulation - John L. Rayner; Mike J. Donn; Greg B. Davis; Trevor P. Bastow; Kaveh Sookhak Lari; Colin D. Johnston; Andrew King; Andrew Furness (Science of The Total Environment, 2024)

Atmospheric and advective forcing of upwelling on South Africa's central Agulhas Bank - Lisa Hancke; David Smeed; Mike Roberts; Cristina Russo; Darren Rayner; Fatma Jebri (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

RETRACTED: Effects of environmental impact and nutrition labelling on food purchasing: An experimental online supermarket study - Christina Potter; Rachel Pechey; Brian Cook; Paul Bateman; Cristina Stewart; Kerstin Frie; Michael Clark; Carmen Piernas; Mike Rayner; Susan A. Jebb (Appetite, 2023)